Blockchain for mobile applications - Soe, Paing Thu (Nanyang Technological University, 2020)
Blockchain is a decentralized and public ledger system where people store data of transactions without any centralized party having control. It is a technology that enables data security, transparency, and trust. Since birth in 2008, it has gained extensive popularity in many fields, especially in finance and Information technology. Many technology specialists and leaders often consider blockchain technology as the next fundamental generation of technology. One of the best-known usages of blockchain is cryptographic currencies such as Bitcoin and Ethereum.